1977
DOI: 10.3382/ps.0561972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Grade Animal Fat on Laying Hen Performance and on Metabolizable Energy of Rations

Abstract: The addition of 2 or 4% fat to laying hen rations based on corn, oats, barley or combinations of these grains significantly (P<0.05) decreased feed consumption and improved feed efficiency. There were no adverse effects of added fat on egg production and on livability of laying hens. When no fat was added, the use of combinations of oats and corn (24.2 and 49.2% of the ration, respectively) or barley and corn (24.2 and 49.2% of the ration, respectively) resulted in an increase in egg production and an improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
3
16
1
Order By: Relevance
“…There was no incidence of fatty liver hemmorhagic syndrome. In general, the production responses of hens during the current study agree with those reported by Lillie et al, 1952;Gerry, 1963;Sell et al, 1976;and Horani and Sell, 1977.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…There was no incidence of fatty liver hemmorhagic syndrome. In general, the production responses of hens during the current study agree with those reported by Lillie et al, 1952;Gerry, 1963;Sell et al, 1976;and Horani and Sell, 1977.…”
Section: Resultssupporting
confidence: 94%
“…The hens were placed in individual cages equipped for collection of excreta. These were used to determine the ME content of the experimental rations according to the procedures described by Horani and Sell (1977).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is logical to assume that the beneficial effect of high fat diets on heat stressed chicks results largely from the associative dynamic effect of such diets. There is now sufficient evidence to show that the associative dynamic effect, originally attributed simply to a decrease in heat increment when dietary mixtures contained fat (Forbes and Swift, 1944), may also include a component of increased metabolizable energy (Leeson and Summers, 1976;Horani and Sell, 1977). This has been demonstrated by an increase in determined metabolizable energy over calculated values when low levels of fat were included in the diet.…”
Section: Discussionmentioning
confidence: 92%
“…The magnitude of improvements is considered to be a reflection of increased metabolizable energy (ME) concentration of the diet. Recently, data have been presented indicating that the generally recognized ME values for feed-grade fats underestimate fat's true energy contribution to practical rations (Touchburn and Naber, 1966;Jensen et al, 1970;Horani and Sell, 1977a). Indeed, Sell et al (1976) and Horani and Sell (1977a,b) found that animal tallow had a ME value approaching or exceeding its gross energy content when used at low levels in laying hen rations.…”
Section: Introductionmentioning
confidence: 91%